(untitled) (World Science, 2019)
Asthma constitute a significant cause of morbidity worldwide and a considerable burden on the health and medical systems of both developed and emerging economies. The article presents the results of the study of the prevalence of asthma symptoms in children of different ages (from 0 to 18 years) in the Kyiv region of Ukraine. Quite high levels of “wheezing in the past 12 months” are noted: 6 mounth-5 years – 24,6%; 6-7 years – 18,7%; 13-14 years – 12,6%; 15-17 years -9,2%. But at the same time, the low level of asthma diagnosis remains an important problem in Ukraine. The levels of asthma symptoms, which may indicate a severe course of the disease, are also quite high. The article presents the results of similar studies in other countries for comparison.